28. SOME FACTORS RELATED TO THE NEED FOR PSYCHOLOGICAL CONSULTATION OF FINAL YEAR MEDICAL STUDENTS AT THAI BINH UNIVERSITY OF MEDICINE AND PHARMACY IN 2022 (Vietnam Journal of Community Medicine, 2024)
Background: Difficulties that arise in student life, if not resolved, can greatly affect physical and psychological health. According to psychologists, to reduce student stress, psychological consultation in schools plays a particularly important role. Objective: Identify factors related to the psychological counseling needs of final-year medical students at Thai Binh University of Medicine and Pharmacy in 2022.Methods: Descriptive research design through cross-sectional survey with 209 students in 5 finalyear medical classes.Results: There is a relationship between gender and academic ranking factors with students’ need for psychological consultation; In which, the rate of female students needing psychological consultation is 1,843 times higher than that of male students (OR=1.843; 95CI:1.015-3.348). Besides, the rate of students with good or poor academic performance needing psychological consultation is only 0.535 times that of students with excellent/good academic performance (OR=0.535; 95CI: 0.305-0.939).Conclusion: Factors related to the need for psychological consultation of final-year medical students at Thai Binh University of Medicine and Pharmacy in 2022 include gender and academic ranking factors.
Keywords: Related factors, Psychological counseling needs, Thai Binh University of Medicine and Pharmacy.